Postharvest physico-chemical and mechanical changes in jambu air (Syzygium aqueum Alston) fruits - Tehrani, M.; Chandran, S.; Hossain, A.B.M.S.; Nasrulhaq-Boyce, A. (2011)
Little data is available in the scientific literature on postharvest changes taking place in Syzygium aqueum fruits, an increasingly popular fruit in the Asian region. In this study the postharvest physico-chemical and mechanical properties, namely, fruit color, weight loss, pulp firmness, total soluble solids, pH and titratable acidity were determined during the postharvest storage period under ambient conditions of Syzygium aqueum fruits. It was observed that weight loss, total soluble solids (TSS) and pH of the jambu air fruits increased with time whilst pulp firmness and the color index of the fruits decreased. Analysis of the antioxidant activity, determined in the methanol extracts of the jambu fruit extracts over a period of 18 days after harvesting, using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, showed that the antioxidant activity increased gradually during postharvest ripening. The total phenol content determined by the Folin-Ciocalteau method revealed a high concentration of phenol content in the jambu air fruits, with values around 344.25+/-107.68 mg gallic acid equivalent (GAE) / 100g fresh fruit. Similarly, the flavonoid content measured spectrophotometrically, using the aluminium chloride colorimetric assay, also showed an increasing trend over the same period. The results were expressed as mg of ascorbic acid equivalent (AAE), gallic acid equivalent (GAE) and catechin equivalent (CE) per 100g of sample. These results represent new data on postharvest changes occurring in Syzygium aqueum fruits and show that this increasingly popular fruit has great potential for future development in the agriculture sector.